Comparative Analysis of the Determinants of Private Investment in WAEMU and CAEMU Zones - HOUNSOU, RÉMY (My University, 2019)
Private investment and public investment are important factors in economic growth and the fight against poverty. Private investment remains an essential link in the economic flow and makes it possible to create wealth. This study uses panel data covering the period 2007-2017 to conduct a comparative analysis of the determinants of private investment in the WAEMU and CAEMU zones. The empirical results based on the OLS and FMOLS estimators are summarized as follows: (1) The variables are mostly non-stationary in level, but there is a long-term cointegration relationship between them making private investment a stable function; (2) The results obtained from the FMOLS method are more robust than those obtained from the OLS method through the significance of the coefficients of the explanatory variables; (3) At the CAEMU level, more variables explain the variation of private investment than at the WAEMU level and the elasticities of the variables of the CAEMU zone are higher than those of the variables of the WAEMU zone.
Keywords: public investment; WAEMU; CAEMU; panel data.